The first term in our arithmetic sequence = 13
The common difference of our arithmetic sequence = 17 - 13 = 4
The formula for finding an equation for any arithmetic sequence is a(n) = A + B(n - 1)
A = the first term
B = the common difference.
Let's plug our numbers in.
a(n) = 13 + 4(n - 1)
Let's check to make sure we're correct.
a(1) = 13 + 4(1 - 1) = 13 + 4(0) = 13 + 0 = 13
a(2) = 13 + 4(2 - 1) = 13 + 4(1) = 13 + 4 = 17
That verifies that our formula is correct.
In conclusion,
a(n) = 13 + 4(n - 1)